2018
DOI: 10.1108/acmm-10-2017-1857
|View full text |Cite
|
Sign up to set email alerts
|

Studying effect of plantain extract behavior as an eco-friendly corrosion inhibitor on the mild steel in 1 M HCl solution

Abstract: Purpose Corrosion inhibitors most commonly are used in the acid pickling, cleaning and etching solutions. Plant extracts as rich and cheap resources are among the eco-friendly inhibitors. This study aims to investigate the inhibition effect of plantain extract on mild steel corrosion. Design/methodology/approach The inhibition influence of plantain extract on mild steel corrosion was investigated through Tafel polarization, electrochemical impedance spectroscopy and weight loss techniques in 1 M HCl solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The values showed that the inhibitors presented negative free energy of adsorption, indicating that the inhibitors were stable ones, and their reaction was spontaneous in the forward direction. The inhibitors also influenced the reaction to having the free energy values less negative than 20 kJ mol -1 , an indication that the reaction followed a physical adsorption mechanism [19][20][21][22][23][24][25][35][36][37][38][39]50,52], and this had been already confirmed from the data obtained for activation energy (Ea) and adsorption enthalpy (∆H).…”
Section: Thermodynamicsmentioning
confidence: 53%
See 2 more Smart Citations
“…The values showed that the inhibitors presented negative free energy of adsorption, indicating that the inhibitors were stable ones, and their reaction was spontaneous in the forward direction. The inhibitors also influenced the reaction to having the free energy values less negative than 20 kJ mol -1 , an indication that the reaction followed a physical adsorption mechanism [19][20][21][22][23][24][25][35][36][37][38][39]50,52], and this had been already confirmed from the data obtained for activation energy (Ea) and adsorption enthalpy (∆H).…”
Section: Thermodynamicsmentioning
confidence: 53%
“…This is due to the high-temperature effects that bring about agitation and desorption of weakly bounded inhibitor molecules held on the low carbon steel surface by van der Waals forces of attraction rather than ionic bonding [13,22,[27][28][29][30]. This can also be possible because of the migration of segments of molecules or individual molecules (inhibitors) in jumps, from one place in a site to a vacant hole of the site [17,25,31].…”
Section: Gasometric Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical analysis (Es’haghi et al , 2018) was performed on an electrochemical work station setup using a conventional three-electrode assemblage in a glass cell of 100-mL capacity. Low carbon steel rod implanted in thermoplastic resin with an uncovered surface area (1 cm 2 ) and platinum foil were used as the working electrode and the counter electrode, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Corrosion is one of the most serious problems in the iron and steel industries [1,2]. Acid solutions such as HCI and H 2 SO 4 , which are commonly used in the steel pickling, cause corrosion of metals [3,4]. Unfortunatelly, there is no method to completely eliminate the corrosion process.…”
Section: Introductionmentioning
confidence: 99%